State, trust, and corporation - Maitland, Frederic William, 1850-1906.; Runciman, David; Ryan, Magnus (Cambridge, UK ; New York : Cambridge University Press, 2003)
Maitland's late, great essays on the historical origins of the state are collected in this volume. They contain a series of profound insights into the way the character of the state has been shaped by the non-political associations that exist alongside it - matters of continuing relevance today.
Machine generated contents note: 1. Corporation Sole -- 2. Crown as Corporation -- 3. Unincorporate Body -- 4. Moral Personality and Legal Personality -- 5. Trust and Corporation.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Maitland, Frederic William, -- 1850-1906.; Maitland, Frederic William, -- 1850-1906; Law -- England; Corporation law -- England; State, The; Droit -- Angleterre; État.; Sociétés -- Droit -- Angleterre -- Législation.; LAW -- Jurisprudence; LAW -- General Practice; LAW -- Reference; LAW -- Essays; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; Corporation law; Law; State, The; England; Staat; Entstehung; Körperschaft; Recht; État.; Fiducie; Sociétés -- Droit